BULLETIN OF THE GEOLOGICAL SOCIETY OF GREECE VOLUME L - of Greece, Geological Society (Bulletin of the Geological Society of Greece, 2016)
14TH INTERNATIONAL CONGRESS OF THE GEOLOGICAL SOCIETY OF GREECE Under the auspices of the Ministry of Education, Research and Religious Affairs